Pathophysiological Consequences of At-Risk Alcohol Use; Implications for Comorbidity Risk in Persons Living With Human Immunodeficiency Virus - Simon, Liz; Edwards, Scott; Molina, Patricia E. (Frontiers in Physiology, 2022)
Heavy alcohol use is a significant risk factor associated with multisystemic pathophysiological effects leading to multiorgan injury and contributing to 5.3% of all deaths worldwide. The alcohol-mediated cellular and molecular alterations are particularly salient in vulnerable populations, such as people living with HIV (PLWH), diminishing their physiological reserve, and accelerating the aging process. This review presents salient alcohol-associated mechanisms involved in tissue injury and exacerbation of cardiometabolic and neuropathological comorbidities and their implications in the context of HIV disease. A novel aspect that the review integrates is the consideration of environmental factors, such as consumption of a western diet to alcohol-induced tissue injury. Alcohol-mediated major mechanisms that contribute to cardiometabolic comorbidity include impaired substrate utilization and storage, endothelial dysfunction, dysregulation of the renin-angiotensin-aldosterone system, and hypertension. Hyperactivation of the hypothalamic-pituitary-adrenal axis and dysregulation of glucocorticoid signaling in vulnerable areas of the brain significantly contribute to alcohol-associated development of neurological deficits and alcohol use disorder risk. Thus, evidence indicates that in PLWH, at-risk alcohol use exacerbates cardiometabolic and neurocognitive pathologies that accelerates biological aging leading to the development of geriatric comorbidities manifested as frailty.